Development of a web-based academic time management system - Mohamed Udin, Zulkifli; Che Mohamed Arif, Ahmad Suki; Md Saman, Azmi (2001)
Web-based systems are widely used in organisational management.The research paper reports on how Web-based technology is used in developing an academic time management system.This prototype system, which is currently used in the School of Information Technology at the Universiti Utara Malaysia, has significantly improved time management. Through this Web-based application, users could manage their time for traditional meetings, student consultations and lectures. Furthermore, this application would enable users to discuss things collaboratively, design projects and conduct meetings through a virtual environment.This research also discovered some constraints and limitations of the system. Finally, an avenue for further research is also identified